Magnetic resonance imaging of tumor with a self-traceable polymer conjugated with an antibody fragment. Issue 13 (1st July 2015) - Yamada, Hisatsugu; Hasegawa, Yoshinori; Suzuki, Yuki; Imai, Hirohiko; Matsuda, Tetsuya; Kimura, Yu; Toshimitsu, Akio; Aoyama, Yasuhiro; Kondo, Teruyuki
Graphical abstract